2016
DOI: 10.1155/2016/5871313
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Obesity and Excessive Gestational Weight Gain on Maternal and Infant Outcomes in Maine: Analysis of Pregnancy Risk Assessment Monitoring System Results from 2000 to 2010

Abstract: The objective of this study is to understand the relationships between prepregnancy obesity and excessive gestational weight gain (GWG) and adverse maternal and fetal outcomes. Pregnancy risk assessment monitoring system (PRAMS) data from Maine for 2000–2010 were used to determine associations between demographic, socioeconomic, and health behavioral variables and maternal and infant outcomes. Multivariate logistic regression analysis was performed on the independent variables of age, race, smoking, previous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 51 publications
3
29
1
3
Order By: Relevance
“…Our observation of no increased risk of adverse birth outcomes (preterm birth, LBW, stunting and small head circumference) among high pre-pregnancy BMI women is consistent with a retrospective study of Thai women [ 31 ]. By contrast, several other studies, as well as a systematic review, reported that high pre-pregnancy BMI (>25kg/m 2 ) increased the risk of preterm delivery [ 7 , 28 , 32 ]. However, it is important to note that some of those studies used different cut off points in describing BMI categories.…”
Section: Discussionmentioning
confidence: 95%
“…Our observation of no increased risk of adverse birth outcomes (preterm birth, LBW, stunting and small head circumference) among high pre-pregnancy BMI women is consistent with a retrospective study of Thai women [ 31 ]. By contrast, several other studies, as well as a systematic review, reported that high pre-pregnancy BMI (>25kg/m 2 ) increased the risk of preterm delivery [ 7 , 28 , 32 ]. However, it is important to note that some of those studies used different cut off points in describing BMI categories.…”
Section: Discussionmentioning
confidence: 95%
“…According to a recent review, TGWG above or below the recommended range has been associated with adverse maternal and child outcomes, such as prematurity [ 39 ]. However, no studies were found relating VAD to TGWG in post-bariatric pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidly obese women have been linked with high risk for pregnancy complications including preeclampsia, hypertension, preterm labor, and gestational diabetes. 29,30 The association between maternal obesity and impaired trophoblast functions including altered trophoblast invasion is also well established. 31 During pregnancy, the high metabolic activity of the placenta is associated with a state of inflammation in turn giving oxidative stress.…”
Section: Discussionmentioning
confidence: 99%